MICROTEACHING - A TOOL USED TO IMPROVE TEACHING SKILLS AND TEACHING BEHAVIOR IN POST GRADUATE STUDENTS - A. Indurkar, Vishal; Emekar, Supriya M.; J. Rafaliya, Nilesh; Bharswadkar, Manik; Gosavi, Ramesh M. (International Journal of Clinical and Biomedical Research, 2017)
Background: Medical teachers most often do not receive a special training in pedagogic techniques. Lack of such training results in ineffectivity of the delivered lecture, communication gap between the teacher and the student, which ends up in lowering the quality of teaching and standard of education. "Micro Teaching" technique is used with the aim of helping budding teachers to sharpen their teaching skills and teaching behaviors. Aims & Objective: To inculcate teaching skills and teaching behaviors in Postgraduate (PG) students and to develop the interest in teaching of PG students. Methodology: It was descriptive longitudinal study on eight first year PG student from various department of our institute. It was a four week study each participant underwent two sessions, in first session 10 minute presentation by participants in front of peer group, followed by peer group feedback on teaching skills, second session two weeks later after incorporating suggestions of first session to see the improvement. After second session participants asked to fill "self-evaluation" forms. Results: After comparing first session with second session results it was found statistically significant improvement in teaching skills and everyone agreed that microteaching helps to improve teaching skills and teaching behaviors, develop interest in teaching and boost confidence. Conclusion: This study has confirmed earlier research findings regarding the benefits of the microteaching technique in assisting individuals to develop their professional competence and confidence. Keywords: Microteaching; Teaching-Learning methods; Teach-re-Teach; Small group teaching.